Who accesses surgery at district level in sub‐Saharan Africa? Evidence from Malawi and Zambia. Issue 12 (22nd November 2017) - Gajewski, Jakub; Dharamshi, Rachel; Strader, Michael; Kachimba, John; Borgstein, Eric; Mwapasa, Gerald; Cheelo, Mweene; McCauley, Tracey; Bijlmakers, Leon; Brugha, Ruairi
Abstract: Objectives: To examine age and gender distribution for the most common types of surgery in Malawi and Zambia. Methods: Data were collected from major operating theatres in eight district hospitals in Malawi and nine in Zambia. Raw data on surgical procedures were coded by specialist surgeons for frequency analyses. Results: In Malawi female surgical patients had a mean age of 25 years, with 91% aged 16–40 years. Females accounted for 85%, and obstetric cases for 75%, of all surgical patients. In Zambia, female surgical patients had a mean age of 26, with 75% aged 16–40 years. They accounted for 55% of all cases, 34% being obstetric. Male surgical patients in Malawi were on average older (33 years) than in Zambia (23 years). General surgical cases in men and women, respectively, had a median age of 42 and 32 in Malawi and 26 and 30 in Zambia. The median age of trauma patients was 12 in males and 10 in females in both countries. Children aged 0–15 years accounted for 64–65% of all trauma cases in Malawi and 57–58% in Zambia, with peak incidences in 6‐ to 10‐year‐olds. Conclusions: Women of reproductive (16–45 years) mainly undergoing Caesarean sections and children aged 0–15 years who accounted for two‐thirds of trauma cases are the main patient populations undergoing surgery at district hospitals in Zambia and Malawi. Verification and analysis of routine hospital data, across 10–30% of districts countrywide, demonstrated the need to prioritise quality assurance in surgery and anaesthesia, and preventive interventions in children.